Peristiwa Alam dalam Peribahasa Madura sebagai Ekspresi Masyarakat Madura - khoiri M.; Supratman Muhammad Tauhed; Julian Royyan; Rahmad Rahmad; Putri Irmalia; Islam Rofi’ati Nur Diana (Science and Education Journal (SICEDU), 2026)
This study aims to examine the representation of natural phenomena in Madurese proverbs as expressions of Madurese cultural identity. Madurese proverbs embody reflections of a worldview that emerges from the intense interaction between humans and a harsh, arid natural environment. Natural phenomena such as rain, drought, waves, and wind are employed as metaphors to convey moral, social, and behavioral values that shape the social order of the community. A qualitative approach using an ecolinguistic and anthropolinguistic framework was applied to interpret thirteen proverbs selected from Kamus Lengkap Bahasa Indonesia–Madura by Adrian Pawitra. The findings reveal that Madurese proverbs containing elements of natural phenomena function as a medium for internalizing values and ecological wisdom. First, moral values are reflected through natural symbols that emphasize the importance of honesty, perseverance, and patience. Second, social values are evident in proverbs that highlight balance, solidarity, and collective responsibility. Third, behavioral values are associated with work ethic, discipline, and adaptive capacity in facing life’s challenges. Madura proverbs capture local knowledge and life philosophy, presenting ecological wisdom that is essential for cultural preservation and value-based education.